2013
DOI: 10.7314/apjcp.2013.14.3.1829
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Cytotoxic Activity of Seed Oil of Fenugreek Against Various Cancer Cell Lines

Abstract: In the present study, investigations were carried out to screen the anticancer activities of fenugreek seed oil against cancer cell lines (HEp-2, MCF-7, WISH cells), and a normal cell line (Vero cells). Cytotoxicity was assessed with MTT and NRU assays, and cellular morphological alterations were studied using phase contrast light microscopy. All cells were exposed toi 10-1000 μg/ml of fenugreek seed oil for 24 h. The results show that fenugreek seed oil significantly reduced the cell viability, and altered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 17 publications
1
15
0
Order By: Relevance
“…This is also supported by the earlier findings where fenugreek crude seed extract was selectively toxic to cancer cell lines and not harmful to the normal counterparts but purified components such as diosgenin were toxic to both normal and cancer cell lines (49). This selective cytotoxicity was also observed in the oil extracted from fenugreek seeds (50). Recently, Dick et al, reported the mechanism of ASC filament formation and signal amplification for inflammasome mediated cytokine production (48).…”
Section: Discussionsupporting
confidence: 66%
“…This is also supported by the earlier findings where fenugreek crude seed extract was selectively toxic to cancer cell lines and not harmful to the normal counterparts but purified components such as diosgenin were toxic to both normal and cancer cell lines (49). This selective cytotoxicity was also observed in the oil extracted from fenugreek seeds (50). Recently, Dick et al, reported the mechanism of ASC filament formation and signal amplification for inflammasome mediated cytokine production (48).…”
Section: Discussionsupporting
confidence: 66%
“…Both aqueous and ethanolic extracts exerted cytotoxic effects against MCF-7 cells in a dose- and time-dependent manner (Sebastian and Thampan, 2007), while an ethanolic extract induced cell death in Jurkat leukemia cells (Al-Daghri et al, 2012). Seed oil from fenugreek induced cytotoxicity toward several cancer cell lines [HEp2 (human epidermoid cancer cells), WISH, and MCF-7; Al-Oqail et al, 2013]. …”
Section: Scientific Evidence and Mechanisms Of Actionmentioning
confidence: 99%
“…The pharmacological evidence has demonstrated that fenugreek possesses antiviral, antimicrobial, antioxidant, antidiabetic, anti-inammatory, antihypertensive, antihyperlipidemic, and antitumor activities. [32][33][34][35][36] The fenugreek seed contains a variety of chemical constituents that include alkaloids (such as trigonelline, gentianine, carpaine, etc. ), furastanols (like vicenin-1, vitexin, diosgenin, gitogenin, yamogenin), free amino acids (4-hydroxyisoleucine), protein, mucilaginous soluble ber and insoluble ber, xed fatty acids, essential oils, steroidal saponins, etc.…”
Section: Introductionmentioning
confidence: 99%